Challenges and Efforts of Financial Management Systems in Private Universities in Indonesia - Silvius Rejaan (International Conference on Science, Education, and Technology, 2023)
This study aims to analyze and examine the financial management system in private universities. As an educational institution, of course the main focus of private tertiary institutions is to create quality graduates who are useful for the nation and state. In an effort to improve the quality of education, a private tertiary institution must be able to manage and manage finances in a transparent and good manner so that usage can proceed according to a predetermined plan. Budget management is often a problem, because private tertiary institutions often fail or are not effective and efficient in managing the budget resulting in various problems, such as inadequate infrastructure, lecturer and staff salaries below the district/city minimum wage, lecturer competency still lacking because they have never participated in training or technical guidance as well as on the quality competence of graduates at private tertiary institutions. So that there is a need for changes related to good financial management in order to create an increase in the quality of education in private tertiary institutions. This research is expected to be one of the solutions for the implementation of good financial management in private universities.